2007
DOI: 10.1016/j.neuroimage.2006.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of activation center in the brain during muscle fatigue: An explanation of minimal central fatigue?

Abstract: Accumulating evidence suggests that the overall level of cortical activation controlling a voluntary motor task that leads to significant muscle fatigue does not decrease as much as the activation level of the motoneuron pool projecting to the muscle. One possible explanation for this "muscle fatigue>cortical fatigue" phenomenon is that the brain is an organ with built-in redundancies: it has multiple motor centers and parallel pathways, and the center of activation may shift from one location to another when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 45 publications
3
55
0
2
Order By: Relevance
“…As proposed by Liu, et al (2007), when one group of active cortical neurons becomes fatigued, another population of neurons might take over the function, so that the descending command to the motoneuron pool could continue without significant compromise. The spread of activation in the M1 in this case would be a strategy of the brain to prolong the motor task or maintain muscle output after fatigue sets in (Liu, et al, 2007). Fatigue of neurons could be affected by intrinsic adaptations of cells in responding to a continuous stimulation or static activation (Kernell & Monster, 1982;Sawczuk, Powers, & Binder, 1995), reflex inhibition, or input from other sources, such as sensory feedback (Garland & Kaufman, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by Liu, et al (2007), when one group of active cortical neurons becomes fatigued, another population of neurons might take over the function, so that the descending command to the motoneuron pool could continue without significant compromise. The spread of activation in the M1 in this case would be a strategy of the brain to prolong the motor task or maintain muscle output after fatigue sets in (Liu, et al, 2007). Fatigue of neurons could be affected by intrinsic adaptations of cells in responding to a continuous stimulation or static activation (Kernell & Monster, 1982;Sawczuk, Powers, & Binder, 1995), reflex inhibition, or input from other sources, such as sensory feedback (Garland & Kaufman, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This occurs until the task requires a maximal voluntary effort. The system that increases the motor output from the M1 is known as the facilitation system and is composed of a re-entrant neural circuit that interconnects the limbic system, basal ganglia (BG), thalamus (TH), orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortex (ACC), premotor area (PM), supplementary motor area (SMA), and M1 (Dettmers et al, 1996;Behan, 2000, 2004;Johnston et al, 2001;Liu et al, 2003Liu et al, , 2007Korotkov et al, 2005;Post et al, 2009;. A motivational input to this facilitation system enhances activity in the SMA and then M1, thereby increasing the motor output to the peripheral system .…”
Section: Introductionmentioning
confidence: 99%
“…While the present study focused solely on the activation of the PFC, other brain regions are involved in fatigue development, particularly in older adults (Liu et al, 2003;Clark & Taylor, 2011;Noble et al, 2011). Previous research has demonstrated a shift in activation centers in the brain to maintain neuromuscular performance during a fatiguing protocol (Liu et al, 2007). It is likely that the presence of cognitive fatigue accelerated cortical redistribution in older adults.…”
Section: Discussionmentioning
confidence: 93%
“…Second, the present study monitored the PFC regions due to equipment constraints. Existing neuroimaging investigations of fatigue development suggest a shift in activation centers in the brain to compensate for fatigue-related loss in neural efficiency, particularly with the normal aging process (Liu et al, 2007;Clark & Taylor, 2011;Noble et al, 2011), future research should examine activation of motor function-related brain regions to understand age-related changes in functional brain activation patterns when individuals are physically and cognitively fatigued. Third, while all participants reported that the 60-minute working memory tasks were cognitively fatiguing, it is possible that longer exposure to such stressors may result in greater negative effects of cognitive fatigue on neuromuscular function.…”
Section: Discussionmentioning
confidence: 99%